Referencing International Human Rights Law In Indonesian Constitutional Adjudication - Bisariyadi, Bisariyadi (Constitutional Review, 2018)
The power of the Indonesian Constitutional Court to review laws is a constitutional adjudication process. It is a forum to resolve constitutional issues where a citizen can challenge Law that has injured his rights. The Court's reasoning provides audiences with the debates for its deliberation. Audiences may find reference to the international human rights law. It is an interesting practice. However, there is no studies yet about the information on the statistic of the Court made reference to international human rights law. As such, this study aims to identify reference to international human rights law in the Court's decision on judicial review cases from 2003 to 2016. Additionally, this study also aims to answer the question of what underlies the Court to made reference to international human rights law. As many studies show, the objective of Constitutional Court's references to the international human rights law is to strengthen constitutional rights protection. Nonetheless, the Court did not pay any interests to the global agenda of transnational constitutionalism or a convergence of rights and legal pluralism. The article is divided into 5 (five) sections, commencing with the introduction. The second part discusses the status of international human rights law in Indonesia. As the third presents information on Court's decision which cited international human rights law. Then, the fourth presents typical function of the decision that made reference to international human rights law. It concluded that the practice of referring to international law demonstrates the open attitude of Indonesian constitutional justices to the universal nature of fundamental rights.